2005
DOI: 10.1021/jm040204g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antibacterial Activity of the 4-Quinolone-3-carboxylic Acid Derivatives Having a Trifluoromethyl Group as a Novel N-1 Substituent

Abstract: Novel 1-trifluoromethyl-4-quinolone derivatives (8a,b) were synthesized, and the antibacterial activity of each was evaluated. An oxidative desulfurization-fluorination reaction was employed to introduce a trifluoromethyl group at the N-1 position as a key step. Among the derivatives, 8a was found to exhibit antibacterial activity comparable to that of norfloxacin (1) against Staphylococcus aureus Smith, Streptococcus pneumoniae IID1210, and Escherichia coli NIHJ JC-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 13 publications
1
21
0
5
Order By: Relevance
“…[9] Moreover,apromising isolated study found the N-CF 3 analogue of floxacin to retain similar antibacterial activities as its methylated counterpart. [10] We herein demonstrate the rapid and selective formation of awide range of trifluoromethylated amines from secondary amines.T he high-yielding,o ne-pot strategy is based on apolarity inversion and in situ formation of athiocarbamoyl fluoride intermediate using the bench-stable (Me 4 N)SCF 3 reagent.…”
mentioning
confidence: 85%
“…[9] Moreover,apromising isolated study found the N-CF 3 analogue of floxacin to retain similar antibacterial activities as its methylated counterpart. [10] We herein demonstrate the rapid and selective formation of awide range of trifluoromethylated amines from secondary amines.T he high-yielding,o ne-pot strategy is based on apolarity inversion and in situ formation of athiocarbamoyl fluoride intermediate using the bench-stable (Me 4 N)SCF 3 reagent.…”
mentioning
confidence: 85%
“…Several new derivatives have been synthesized and evaluated for antibacterial activity against many bacterial strains such as P. aeruginosa, K. pneumoniae, S. pneumoniae, S. aureus, S. epidermis etc. [9][10][11][12] Fluoroquinolones analogs with antitubercular [13][14] , anti-fungal 15 , anti-viral 16 activities are well known. Many research endeavours are being undertaken to elaborate the possible role of fluoroquinolones in carcinogenesis and mutagenesis [17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…

Die Bedeutung fluorierter Moleküle in der Chemie hat in den letzten Jahren rasch zugenommen. [4] Demzufolge sollten sie sich auch in ihren physikalischen, chemischen und/oder biologischen Eigenschaften erheblich unterscheiden.In einer einmaligen medizinalchemischen Arbeit ersetzten Asahina et al [5] in Norfloxacin und Ciprofloxacin, zwei wichtigen chemotherapeutischen antibakteriellen Mitteln, formal den Alkylsubstituenten auf dem 4-Chinolonstickstoffatom durch eine CF 3 -Gruppe und zeigten damit, dass in diesem Fall die Trifluormethylgruppe einen ähnlichen Effekt auf die antibakteriellen Eigenschaften ausübt wie eine einfache Methylgruppe. Darüber hinaus bestand die Hälfte der zehn meistverkauften rezeptpflichtigen Arzneimittel des Jahres 2005 aus fluorierten Molekülen.

…”
unclassified
“…In einer einmaligen medizinalchemischen Arbeit ersetzten Asahina et al [5] in Norfloxacin und Ciprofloxacin, zwei wichtigen chemotherapeutischen antibakteriellen Mitteln, formal den Alkylsubstituenten auf dem 4-Chinolonstickstoffatom durch eine CF 3 -Gruppe und zeigten damit, dass in diesem Fall die Trifluormethylgruppe einen ähnlichen Effekt auf die antibakteriellen Eigenschaften ausübt wie eine einfache Methylgruppe. Der CF 3 -Substituent wurde durch oxidative Desulfurierung/Fluorierung eines entsprechenden Dithiocarbamats eingeführt (Schema 1).…”
unclassified